Persepsi Mahasiswa Program Studi Manajemen Keuangan Sektor Publik Terhadap Green Finance Sebagai Bagian dari Pendidikan Keuangan - Fitrasari, Raisa Dea; Zakiyatul Amaliyah; Parlis Lawalata; Rachman Hadi (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
Environmental pollution and excessive exploitation of natural resources emphasize the urgency of implementing sustainable development through the concepts of green economy and green finance. In higher education, students' understanding and perceptions of green finance are crucial factors in developing sustainable financial literacy, particularly for prospective public sector financial managers. This study aims to analyze the perceptions of students in the Public Sector Financial Management Study Program regarding green finance as part of financial education. A descriptive quantitative method was used, involving 48 students selected through purposive sampling. Data were collected using a questionnaire measuring three dimensions of perception: knowledge, attitude, and readiness toward green finance. The data were then analyzed using descriptive statistics. The results showed that students' perceptions were high across all dimensions, with an average knowledge score of 3.81, attitude score of 4.33, and readiness score of 4.17. These findings indicate that students have a good understanding, positive attitudes, and readiness to implement green finance principles in public sector finance. Therefore, the integration of green finance in financial education needs to be continuously strengthened to support sustainable public sector financial management.